2017
DOI: 10.1371/journal.pone.0176913
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of corneal asphericity (Q value) and its related factors of 1,683 Chinese eyes older than 30 years

Abstract: PurposeTo determine corneal Q value and its related factors in Chinese subjects older than 30 years.DesignCross sectional study.Methods1,683 participants (1,683 eyes) from the Handan Eye Study were involved, including 955 female and 728 male with average age of 53.64 years old (range from 30 to 107 years). The corneal Q values of anterior and posterior surfaces were measured at 3.0, 5.0 and 7.0mm aperture diameters using Bausch & Lomb Orbscan IIz (software version 3.12). Age, gender and refractive power were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 23 publications
5
33
2
Order By: Relevance
“…Regarding posterior surface Q, not all available studies including the present investigation found a significant relationship with sex. 23,30 Thus, corneal asphericity appears to be equivalent in men and women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding posterior surface Q, not all available studies including the present investigation found a significant relationship with sex. 23,30 Thus, corneal asphericity appears to be equivalent in men and women.…”
Section: Discussionmentioning
confidence: 99%
“…2 Various reasons can be proposed for these discrepancies in the reported Q values, including differences in ethnicity, age distribution, sample size, measurement equipment and chord diameter. As seen in Table 6, most previous investigations had a small sample size with only two studies 4,30 having a sample of more than 1,000 eyes. This reduces the generalizability of the findings to some extent, although the sample size is, in part, dependent on the study aims, objectives and context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without the influence of the corneal flap, the comparison between the SMILE and LASEK is more like the comparison of femtosecond laser and excimer laser, and the different corneal-tissue-removing pattern, and which treatment inducing less asphericity change and better visual quality remained unclear. The corneal ashphericity could be represented by the corneal Q value, and could also be reflected by the change of corneal power from center to periphery [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…[ 33 , 34 ] Q value mathematically reflects corneal asphericity, which can be defined to variations in radius of curvature from apex to periphery. [ 35 , 36 ]…”
Section: Discussionmentioning
confidence: 99%